2020
DOI: 10.1111/ppc.12576
|View full text |Cite
|
Sign up to set email alerts
|

Problematic social media use and mental health (depression, anxiety, and insomnia) among Lebanese adults: Any mediating effect of stress?

Abstract: Purpose: To examine the association between problematic social media use with depression, anxiety, insomnia, and stress in a sample of young Lebanese adults.Methods: This cross-sectional study was achieved between January and May 2019; 466 out of 600 adults completed the questionnaire.Results: Higher problematic social media use was significantly associated with higher depression, anxiety, and insomnia, but not stress. Stress mediated the relation between depression, anxiety, insomnia, and problematic social m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
32
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 90 publications
(94 reference statements)
9
32
1
2
Order By: Relevance
“…Furthermore, in the FMS patients with greater sleep disorders, the FMS disease severity and pain scores were determined to be higher. Interestingly, contrary to previous studies, this study did not find a significant relationship between sleep disorders and social media addiction [34][35][36]. This may be because previous studies included people who did not have FMS or any disease and found that excessive social media use causes sleep disturbance.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, in the FMS patients with greater sleep disorders, the FMS disease severity and pain scores were determined to be higher. Interestingly, contrary to previous studies, this study did not find a significant relationship between sleep disorders and social media addiction [34][35][36]. This may be because previous studies included people who did not have FMS or any disease and found that excessive social media use causes sleep disturbance.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that higher depressive temperament was significantly associated with more phubbing, in accordance with a previous study [32]. Similar results were found in many previous studies where smartphone addiction and Internet addiction were found associated with higher depression [19,20,52]. In fact, many studies has showed a strong association between many temperament characteristics and increased risk of depression [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…Study‐independent clinical psychologists carried out the data collection and evaluated the psychiatric conditions of participants. The methodology adopted in this study project is similar to that used in previous studies 19–21 …”
Section: Methodsmentioning
confidence: 99%
“…The methodology adopted in this study project is similar to that used in previous studies. [19][20][21]…”
mentioning
confidence: 99%